Nanostructured materials : processing, properties, and applications - Koch, C. C. (Materials science and process technology series., 2007)
Nanostructured materials are one of the highest profile classes of materials in science and engineering today, and will continue to be well into the future. Potential applications are widely varied, including washing machine sensors, drug delivery devices to combat avian flu, and more efficient solar panels. Broad and multidisciplinary, the field includes multilayer films, atomic clusters, nanocrystalline materials, and nanocomposites having remarkable variations in fundamental electrical, optic, and magnetic properties. Nanostructured Materials: Processing, Properties and Applications, 2nd Edition is an extensive update to the exceptional first edition snapshot of this rapidly advancing field. Retaining the organization of the first edition, Part 1 covers the important synthesis and processing methods for the production of nanocrystalline materials. Part 2 focuses on selected properties of nanostructured materials. Potential or existing applications are described as appropriate throughout the book. The second edition has been updated throughout for the latest advances and includes two additional chapters.